Thermal and calorimetric investigations of titania–silica composites - B Charmas; J Skubiszewska-Zięba; H Waniak-Nowicka (Adsorption Science & Technology)
The paper presents the studies of effects of TiO 2 amount differentiation on the structural and thermal properties of titania–silica complex oxides prepared by chemical vapor deposition of TiCL 4 onto the Si-40, Si-60, and Si-100 silica gels. The mesoporous materials, characterized by a varied pore structure with highly developed surface and large pore volume, were obtained. The porous structure of materials under investigations was characterized by the low-temperature nitrogen adsorption–desorption method as well as by power spectral density calculated from the calorimetric investigations of water confined in the pores. Moreover, the thermodesorption of water using the quasi-isothermal thermogravimetry was used to characterize their thermal and surface properties. The adsorbed water layers and the concentration of weakly and strongly bound water as well as the surface free energy on the adsorbent–water interfaces were calculated. It was stated that the increase of titania content causes a gradual decrease of specific surface area and has a significant effect on the porous structure formation. The water thermodesorption from the surface proceeds in few stages because of the porosity created by TiO 2 . The decrease in the total surface free energy (Δ G Σ ) can be observed with the increasing TiO 2 content. The largest Δ G Σ value at the adsorbent/strongly bound water interface is exhibited by the adsorbents of Si-100 series. The lowering of the freezing/melting points of water contained in the pores of the studied materials is strongly connected with their porous structure.